Pengaruh Kualitas Pelayanan terhadap Loyalitas Pelanggan di Rental Mobil CV. Ilham Motor Gandu Mlarak Ponorogo - Dhika Amalia (Al Tijarah, 2015)
The purpose of this study was to determine the amount of quality customer service and loyalty to know a very dominant factor affecting customer loyalty in the CV . Ilham Motor. This research method is the primary data from the questionnaires , sampling technique is a technique associated with customer 100 CV Ilham Motor . Data analysis is a quantitative method to test the validity , reliability testing , multiple linear regression analysis , the correlation coefficient analytic , analytic determination coefficient . And to know the impact of service quality of costumer’s loyalty by T test and F test. The result of double analytic linier regression is obtainable equation Y: 4,413 + 0,144 X1 + 0,026 X2 + 0,162 X3 + 0,151 X4 + 0,223 X5 + e. The result of determination coefficient (R2) is 32.1% and the rest is 67.9% that affected by other variable which is not included in research model. According to T test, the result is that the five costumer service quality (tangibles, reliability, responsiveness, assurance, and empathy) contained by a variable that is not impacted, it is reliability; because Ho is accepted and Ha is rejected, whilst the other four are impacting costumer’s loyalty because Ha is accepted and Ho is rejected. The F test result shows that tangibles, reliability, responsiveness, assurance, and empathy simultaneously have significant effect to costumer’s loyalty because F > F table or 8,898 > 2,33. And, from the five free variable, empathy (X5) is variable that has very dominant effect, the coefficient is 0,223 or 22,3 %.